Electroconvulsive Therapy Handbook - Deisy Santana Castellón; Odalis Fernández López; Juan Rafael Cordero Jiménez; Iris Rodríguez Sánchez; Lenis Cañedo Santana; Rafael Ángel Bello Cruz; Angel Fernández Vidal; Dámaso Molina González (Medisur, 2007)
-